Establishment of conversion coefficient of whole body effective dose by human tissue of electron paramagnetic resonance (EPR). (February 2019) - Liu, Y.C.; Lai, L.H.; Wang, C.F.; Chuang, K.S.; Lu, C.C.; Lin, J.P.; Lin, H.H.
Abstract: Electron paramagnetic resonance (EPR) dosimetry is a physical method for the retrospective dose assessment for radiation accident. It can be used to detect and measure free radical concentration proportional to the absorbed dose of the sample. The purpose of the work is to establish the conversion coefficients between the absorbed dose of tooth/fingernail and the whole body effective dose. The calibration curves of signal-dose for EPR and electric charge-dose for thermoluminescent dosimeter (TLD) were first established. Linear regression of the relationship has a high R-squared (>0.99) for different radiation modalities with different amounts of energy. The Rando phantom with embedded TLDs at each critical organ was irradiated using the photon beams (6, 10 MV) and the electron beams (6, 9, and 12 MeV) from the linear accelerator. Accordingly, the conversion coefficients between tooth/fingernail dose and whole-body effective dose or between tooth/fingernail dose and the organ dose were derived based on the measurements of TLDs. The effective dose and the absorbed dose of organs can be roughly and quickly estimated by employing the proposed conversion coefficients based on the EPR measurements of teeth and fingernails in case of a radiation accident. As such, the radiation injuries those exposed suffer can be identified for categorization using the EPR measurements. Highlights: EPR dosimetry and TL dosimetry were used. Good linear relationships of EPR signals-dose and TLD signals-dose are presented. Conversion coefficients from the tooth/fingernail dose to the effective dose. EPR measurement of teeth and fingernails for predicting the effective/organ dose.